Kajian Kriminologis Tingkat Kejahatan Di Jembatan Merah Putih Kota Ambon - Dilva Sahara Drachman; Hadibah Zachra Wadjo; Lionie Lokollo (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Crime or usually also called criminology is an act or act that violates or does not comply with the values of goodness or holiness that have been agreed upon by members of the community based on religious values or certain regulations.Purposes of the Research: To discuss what factors are the causes of crime at the Merah Putih Bridge (JMP) as well as the prevention efforts carried out by both the police and the community in preventing crime at the Red and White Bridge (JMP) Ambon City. Methods of the Research: This research method is a type of empirical juridical research, or what is commonly referred to as field research which examines the applicable legal provisions and the actions carried out by the community itself in its environment.Results of the Research: The crimes that occurred at the Merah Putih Bridge (JMP) were caused by various factors including the Merah Putih Bridge (JMP) which is the main route so that it is crossed by various kinds of vehicles, potential crowds, economic conditions, lack of attention from the local government and the absence of security posts around the Red and White Bridge (JMP). The form of prevention efforts that must be carried out by the community so that crime does not happen again at Jembatan Merah Putih (JMP) is to not go through it if there is no urgent need. And for the police, they should build security posts around the Red and White Bridge (JMP) and carry out strict guarding. So with this the police can monitor the movements of people who will commit crimes so that they can be prevented so that crime does not occur.